Titanium dioxide nanostructures as efficient photocatalyst: Progress, challenges and perspective. (14th October 2020) - Ijaz, Mohsin; Zafar, Maria
Summary: In the growing energy consumption, the photocatalysis seems to be very helpful due to promising environmental applications. Several semiconducting nanostructures are reported as photocatalysts but still, the researchers are finding a way towards higher efficiency. The TiO2 nanostructures with different sizes, morphologies, synthesis methods and dopants have been reviewed to study their effect on photocatalysis. The TiO2 photocatalysts are presented to be widely used in energy and eco‐friendly applications including water purification, hydrogen production, phenol degradation, Cr(VI) and CO2 reduction. The photostability, accessibility and environmental harmlessness have been presented as a break through towards the global energy crisis due to potential application in photocatalytic hydrogen evolution. Besides variety of useful applications, the efficiency is limited due to wide bandgap, fast charge recombination, and many other factors. The progress of TiO2 photocatalyst along with the limitations underway and their possible solutions have been presented from reported literature. It is predicted that an approach towards highly efficient photocatalyst could be achieved in the form of nanostructured TiO2 . Abstract : The unique properties of TiO2 nanostructures enable extraordinary photocatalytic activity towards energy production (in the form of hydrogen) and environmental applications including degradation of dyes as well as harmful gases. Several useful applications of TiO2 nanostructures with different geometrical parameters and synthesis methods have been reviewed. The problems, limitations and some solutions in the form of perspective are presented.